(c+5)(c-3)=

Simple and best practice solution for (c+5)(c-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (c+5)(c-3)= equation:


Simplifying
(c + 5)(c + -3) = 0

Reorder the terms:
(5 + c)(c + -3) = 0

Reorder the terms:
(5 + c)(-3 + c) = 0

Multiply (5 + c) * (-3 + c)
(5(-3 + c) + c(-3 + c)) = 0
((-3 * 5 + c * 5) + c(-3 + c)) = 0
((-15 + 5c) + c(-3 + c)) = 0
(-15 + 5c + (-3 * c + c * c)) = 0
(-15 + 5c + (-3c + c2)) = 0

Combine like terms: 5c + -3c = 2c
(-15 + 2c + c2) = 0

Solving
-15 + 2c + c2 = 0

Solving for variable 'c'.

Factor a trinomial.
(-5 + -1c)(3 + -1c) = 0

Subproblem 1

Set the factor '(-5 + -1c)' equal to zero and attempt to solve: Simplifying -5 + -1c = 0 Solving -5 + -1c = 0 Move all terms containing c to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1c = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1c = 0 + 5 -1c = 0 + 5 Combine like terms: 0 + 5 = 5 -1c = 5 Divide each side by '-1'. c = -5 Simplifying c = -5

Subproblem 2

Set the factor '(3 + -1c)' equal to zero and attempt to solve: Simplifying 3 + -1c = 0 Solving 3 + -1c = 0 Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1c = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1c = 0 + -3 -1c = 0 + -3 Combine like terms: 0 + -3 = -3 -1c = -3 Divide each side by '-1'. c = 3 Simplifying c = 3

Solution

c = {-5, 3}

See similar equations:

| 2x^2+15x+50=0 | | 0.33(3x+9)=7 | | 2x^2+15x+150=0 | | -x^2+y^2-6x-6y-4=0 | | x-3(x-2)+2(x-1)=4x+3 | | 9=x^2+8x | | 49-4x=14x+17 | | 4(x)-7=45 | | (y-4)-(y+7)=3y | | 8-9x=24-16x | | 0.5(x-4)=3 | | -6a+2+7a=8-28 | | 4[5y-2]=52 | | 10x-4=7x+14 | | -8-3x=12-7x | | 4x-9-x=21 | | 46=2(2w+5)+2w | | 4[y+3]=24 | | 5m+-6n-56nm+89a+56=5 | | 3x+4=(x-7)*8 | | 3x+25=11x-47 | | 3x+4=8x | | 10p-6=-4+6p | | 7h+7h= | | 61-4x=41x+15 | | 7-7x=29-14x | | 3(2p+7)=24 | | 6x+9=17-7x | | 128-3x=6x+12 | | 2(5*6)= | | 5[t-1]=20 | | x=30-y |

Equations solver categories